SCIENTIFIC VIEWS OF EASTERN THINKERS ON LABOR EDUCATION IN THE FAMILY - Turamuratov Ulug'bek Uroqovich; Tangriqulova Ra’no Xo‘shboqovna (Scholar Express Journal, 2023)
This article collects the views of eastern thinkers on labor education, provides information about the role of parents in the development of labor education in the family. The meaning of the concepts of labor education and hard work is revealed
Keywords: Work education; hard work; parents